Representasi Perempuan dalam Lembaga Legislatif di Sumatra Barat Pasca Quota 30% - Fatmariza, Fatmariza (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2005)
This article discusses about representatives of women politician at legislative body in West Sumatera after stating by regulatives that women should represent 30% of members of legislative body.Â The result of this research indicated that general election of 2004 did not success to place 30% of women politician in legislative body. There are only about 8.3% of women politician represented in the body. In several region (kabupaten and kota) there is no political women at the legislative body. This is caused by several factors, such as statement of regulation is interpretable, domination of political men in party leadership, values of social culture are gender, bias, and internal factors of women herself. Kata Kunci: Representasi, Perempuan, Quota 30%